Performance evaluation model for competitive development - PEÑA ALVARADO, Exilda Elena (2020)
Performance evaluation is considered as a systematized process that allows essential actions to be fomulated to carry out work tasks in the company. The study aimed to determine if a performance evaluation design model will improve competitive development. The study methodology was applied, with an explanatory design, the instrument analyzed was the test questionnaire, for administrative workers The results obtained showed that 60% of administrative workers received incentives, 30% always and the other 30% sometimes. It was concluded that there is a tool that measures competitive development and productivity, but that does not show the results of the evaluation at 100%.Keywords: Performance evaluation, competitive development, job skills.